Lower atmosphere and pressure evolution on Pluto from ground-based stellar occultations, 1988-2016 - Meza, E (2019)
This article is dedicated to the memory of H.-J. Bode, J. G. Greenhill and O. Faragó for their long-standing support and participation to occultation campaigns. The work leading to these results has received funding from the European Research Council under the European Community’s H2020 2014-2020 ERC Grant Agreement n° 669416 “Lucky Star”. E.M. thanks support from Concytec-Fondecyt-PE and GA, FC-UNI for providing support during the 2012 July 18 occultation.